Exploring the conceptualization of the sensory dimension of tourist experiences - Agapito, Dora (2014)
This paper aims to contribute to the conceptualization of the sensory dimension of tourist experiences by discussing its theoretical underpinnings. A multidisciplinary approach to the human senses shows their importance to the individual’s experience and perception of the surrounding world, recommending the appropriateness of a holistic analysis of sensescapes in tourism. A review of empirical studies conducted under the experiential paradigm of tourism on the five human senses (sight, hearing, smell, taste, and touch) evinces the use of both qualitative and quantitative methodologies, which depends on research purposes, but also the practical implications of findings and data analysis to destination marketing and management. The paper discusses the role of the senses in designing tourist experiences, and identifies important topics regarding the study of the sensory dimension of tourist experiences, considering future research opportunities.